Overcoming CD226-related immune evasion in acute myeloid leukemia with CD38 CAR-engineered NK cells - Luciana Melo Garcia; Achintyan Gangadharan; Pinaki Banerjee; Ye Li; Andy G.X. Zeng; Hind Rafei; Paul Lin; Bijender Kumar; Sunil Acharya; May Daher; Luis Muniz-Feliciano; Gary M. Deyter; et al. (Cell Reports)
Summary: CD226 plays a vital role in natural killer (NK) cell cytotoxicity, interacting with its ligands CD112 and CD155 to initiate immune synapse formation, primarily through leukocyte function-associated-1 (LFA-1). Our study examined the role of CD226 in NK cell surveillance of acute myeloid leukemia (AML). NK cells in patients with AML had lower expression of CD226. CRISPR-Cas9 deletion of CD226 led to reduced LFA-1 recruitment, poor synapse formation, and decreased NK cell anti-leukemic activity. Engineering NK cells to express a chimeric antigen receptor targeting the AML antigen CD38 (CAR38) could overcome the need for CD226 to establish strong immune synapses. LFA-1 blockade reduced CAR38 NK cell activity, and this depended on the CD38 expression levels of AML cells. This suggests parallel but potentially cooperative roles for LFA-1 and CAR38 in synapse formation. Our findings suggest that CAR38 NK cells could be an effective therapeutic strategy to overcome CD226-mediated immune evasion in AML.